Teratological Effects of Dimethoate on 12th Day Desi Chick Embryo (Gallus gallus domesticus): Dimethoate Toxicity on Chick Embryo - Sabir, Shamila; Ansari, Muhammad Sajjad; Abbas, Muhammad Nadeem; Iqbal, Razia; Iqbal, Javed; Kausar, Saima; Chaudhary, Sadaf (Biological Sciences - PJSIR, 2015)